Implementasi Peraturan Gubernur Jawa Timur Nomor 30 Tahun 2018 Tentang Penyelenggaraan Pendidikan Inklusif Provinsi Jawa Timur - Gangsar Mujiharto; Suwarno Suwarno; Teguh Pramono (Publikasi Indonesia, 2022)
Education is a human need that must be fulfilled. Permendiknas No. 70 of 2009 concerning Inclusive Education for Learners with Disabilities and Potential for Special Intelligence and/or Talent. This research examines the